Barriers to Cardiac Rehabilitation in Ethnic Minority Groups: A Scoping Review - Vanzella, Lais Manata [UNESP]; Oh, Paul; Pakosh, Maureen; Ghisi, Gabriela L. M. (Springer, 2021)
Cardiac rehabilitation (CR) is under-utilized by ethnic minorities. This study aimed to identify barriers associated with referral, enrollment, and completion/adherence of CR for cardiac participants from ethnic minorities. Medline, Embase, Emcare, CINAHL, Pubmed and APA PsycInfo were searched from data inception through January 2020. We excluded studies referring to race minorities, considering barriers reported by providers or family members, and those published in languages other than English or Portuguese. Data was extracted in an individual, provider, and system level. Of 1847 initial citations, 20 studies were included, with most being qualitative in design and classified as good quality. Overall, 12 multi-level barriers were identified in the three CR participation phases, with language being present in all phases. Barriers reported in ethnic minority groups are multi-level. Although identified, literature did not support recommendations to overcome these barriers and clearly more research in this area is needed.
Keywords: Cardiac rehabilitation; Ethnic groups; Minority groups; Treatment adherence and compliance; Health disparities